Giant fibroadenoma of the breast: A case report of a 37-year-old woman during the second trimester of pregnancy - Çitgez, Bülent; Yiğit, Banu; Uçak, Ramazan; Yetkin, Sıtkı Gürkan (Journal of Surgery and Medicine, 2020)
Fibroadenomas are the most common benign breast tumors in young women aged between 20-30 years. Giant fibroadenomas are often larger than 5 cm, weigh more than 500 g or occupy 80% of the breast. They can mimic malignant tumors because they grow rapidly and cause breast deformity. We present a young female patient, in the second trimester of her pregnancy, who had a rapidly growing giant fibroadenoma. Since the mass was suspected of malignancy and caused deformity in the breast, surgical excision was indicated. The operation was performed without complications and the patient was discharged on the second postoperative day. Although the second trimester is suitable for semielective surgeries that cannot be postponed, the timing of the operation is decided by a multidisciplinary team including surgeons, anesthesiologists, obstetricians and perinatologists.